2016
DOI: 10.1055/s-0042-113609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an automated system for endocytoscopic diagnosis of small colorectal lesions: an international web-based study

Abstract: Optical diagnosis of colorectal polyps is expected to improve the cost-effectiveness of colonoscopy, but achieving a high accuracy is difficult for trainees. Computer-aided diagnosis (CAD) is therefore receiving attention as an attractive tool. This study aimed to validate the efficacy of the latest CAD model for endocytoscopy (380-fold ultra-magnifying endoscopy). This international web-based trial was conducted between August and November 2015. A web-based test comprising one white-light and one endocytoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 25 publications
0
84
0
1
Order By: Relevance
“…Thus, a wide variety of CAD systems are available at present. Importantly, the diagnostic accuracy of these novel methods is higher than that achieved by endoscopic diagnosis by less-experienced endoscopists [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a wide variety of CAD systems are available at present. Importantly, the diagnostic accuracy of these novel methods is higher than that achieved by endoscopic diagnosis by less-experienced endoscopists [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…These real-time CAD systems are operated during the actual endoscopic observation. Moreover, Japanese researchers have successfully developed an automated CAD using endocytoscopy based on automated extraction of ultramagnified nuclear features followed by machine-learning analysis from the same group [9][10][11] . Thus, a wide variety of CAD systems are available at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the innovation of AI technology has been accelerating remarkably. In the field of gastroenterology, Mori et al 18 reported a CAD system for the diagnosis of small colorectal polyps. Misawa et al 19 reported a CAD system for the detection of colorectal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…44 In their follow-up study, reported in 2016 and 2018, the diagnostic algorithm was improved by adding texture analysis for feature extraction and a support vector machine as a classifier, thereby producing an output image of the predicted pathology along with the probability of the diagnosis. 45,46 They also developed a more userfriendly CAD system based on endocytoscopy combined with NBI that required no prior staining. 47 This system focused on the analysis of microvessels on the surface of polyps and provided an overall accuracy of 90.0%.…”
Section: Endocytoscopymentioning
confidence: 99%